1997
DOI: 10.1073/pnas.94.4.1366
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-host-disease-associated lymphoid hypoplasia and B cell dysfunction is dependent upon donor T cell-mediated Fas-ligand function, but not perforin function

Abstract: Allogeneic bone marrow transplant recipients often exhibit a graft-versus-host-disease (GVHD )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 36 publications
6
102
0
Order By: Relevance
“…Prior studies have reported lymph node hypoplasia with GVHD (13)(14)(15). In the 1990's, Onoe and Good examined the phenomenon of lymphoid hypoplasia in the setting of subclinical GVHD (4).…”
Section: Discussionmentioning
confidence: 97%
“…Prior studies have reported lymph node hypoplasia with GVHD (13)(14)(15). In the 1990's, Onoe and Good examined the phenomenon of lymphoid hypoplasia in the setting of subclinical GVHD (4).…”
Section: Discussionmentioning
confidence: 97%
“…Inflammatory cytokines and direct antihost cytotoxicity are the main pathogenic factors in the induction of GVHD. Because FasL expression is a major cytotoxic mediator for CD4 ϩ T cells (29,30), we examined the role of ICOS costimulation on FasL expression. Our results highlight the fact that ICOS promotes up-regulation of TCR-driven FasL expression on CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fas ligand (FasL) expression and secretion of Th1 cytokines (i.e., IFN-␥ and TNF-␣) are primary effector functions for CD4 ϩ T cells in inducing GVHD (29,30). To further investigate the mechanisms by which ICOS-blockade ameliorates GVHD, we compared surface expression of FasL on CD4 ϩ T cells from WT or ICOSdeficient donors and found that ICOS Ϫ/Ϫ cells expressed significantly lower levels of FasL than WT cells ( p Ͻ 0.02) (Fig.…”
Section: Icos Enhances Effector Functions Of Cd4 ϩ T Cellsmentioning
confidence: 99%
“…The body of data demonstrating the deleterious effects of GVHR on BM and lymphoid function (13)(14)(15)(16)(17)(18)(19)(20)(26)(27)(28) is often overlooked or underestimated. We previously reported that even low amounts of T cells cause subclinical, yet lympho-depleting, GVHR (25).…”
Section: Discussionmentioning
confidence: 99%